2013
DOI: 10.1007/s12663-013-0536-1
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Elevation with an Alloplastic Material and Simultaneous Implant Placement: A 1-Stage Procedure in Severely Atrophic Maxillae

Abstract: One stage lateral sinus lift procedure with alloplastic bone graft material in combination with 2 stage implant placement has a predictable outcome in patients with severe resorption of posterior maxilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The present results showed a slight significant association between postoperative complications after sinus augmentation and membrane integrity (p=0.0762). Jodia et al 2014 showed that in 15.3% of patients a perforation of the Schneiderian membrane occurred [ 34 ]. The membrane perforation could represent a window for bacterial penetration and invasion into the grafted area.…”
Section: Discussionmentioning
confidence: 99%
“…The present results showed a slight significant association between postoperative complications after sinus augmentation and membrane integrity (p=0.0762). Jodia et al 2014 showed that in 15.3% of patients a perforation of the Schneiderian membrane occurred [ 34 ]. The membrane perforation could represent a window for bacterial penetration and invasion into the grafted area.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the marginal bone loss (MBL) after 6 months postoperatively compared that level at the immediate postoperative period, the average MBL was found to be 0.63 ± 0.18 mm with a minimum of 0.18 mm and maximum of 1.04 mm. Kunal et al in 2014 found that the marginal bone loss in 4 months following sinus augmentation was 0.68 to 1.22 mm (34). It has been mentioned by Klinge et al that MBL greater than or equal to 2 mm at the time of prosthesis delivery in addition to bleeding on probing are considered danger signs and that the case will require intervention (35).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, after evaluating the overall situation of the patient distraction osteogenesis was performed. To facilitate the primary stability of the maxillary implants, sinus elevation procedure, and GBR were also performed [18][19][20]. Contemporary technologies including, 3D CBCT images combined with Amira software package (Mercury Computer Systems, Berlin, Germany) are being used for visuohaptic simulation that allows the surgeon to rapidly experiment with various bone manipulations and plate/distractor configurations.…”
Section: Discussionmentioning
confidence: 99%